Sistem Forum Diskusi Online Warga RW 02 Kelurahan Jati Kecamatan Pulogadung Jakarta Timur - Ratih Wahyuningrum; Rayvin Augusta (RJOCS (Riau Journal of Computer Science), 2018)
Online Discussion Forum System Citizens need to be built as a medium of information exchange and news. With the Online Citizens Discussion Forum System, information and news are faster delivered to citizens wherever and whenever, so it is expected to improve the quality in service for the citizens themselves. To design the Online Discussion Forum System, the author uses PHP programming language with MYSQL database and XAMPP webserver. The system development model used is RAD model with Business Modeling stage, Data Modeling, Process Modeling, Application Generation, Testing and Turnover. The system design tools using UML (Unified Modeling Language) include Use Case Diagram and Activity Diagram. The results obtained from this study are the users of RW 02 residents can interact directly with the Chair RW 02 online and can exchange information online anytime and anywhere with all residents RW 02.